Kinematic connection of forward handspring with learning methods of flight phase - Zivcic Markovic, K. (Croatian Sports Medicine Journal, 2018)
The aim of this study was to determine the correlation of methodological procedures of learning the flight phase in the forward handspring. The study was conducted on one top level gymnast, who performed the forward handspring as well as the methodological methods of learning the flight phase. Forward handspring and six exercises which are chosen for analyses were considered the most suitable for flight phase. For the analysis and comparison of the flight phases of methodical exercises with the flight phase of the forward handspring, most important kinematic variables are chosen. Video recording was performed with two VHS video cameras at a speed of 60 frames per second. Data processing was performed in the APAS (Ariel Performance Analysis System) program. For data processing was used cluster analysis. The results showed a very high statistically significant correlation, between all analyzed methodical exercises for the flight phase with the forward handspring flight phase. The application of such research is possible and advisable at selective categories, where the systematic and timely successive implementation could determine the eventual wrong approach in the methodology of training of basic gymnastic elements that serve as the basis for further upgrading and learning elements of high degree of difficulty value.